An extended ordinary state-based peridynamic approach for modelling hydraulic fracturing. (July 2020) - Zhang, Yubin; Huang, Dan; Cai, Zhuang; Xu, Yepeng
Highlights: Extended state-based peridynamic model and numerical approach for hydraulic fracture analysis. Reflecting fluid–solid interaction and hydraulic pressure on new-born crack surfaces accurately and efficiently. Coupling model with clear physical information and numerical approach with simple operation in practice. Effect of coupling on simulation results, and fracture mechanism of shale with weakness planes. Abstract: An extended ordinary state-based peridynamic model and numerical approach were proposed for modelling fluid–solid interaction and hydraulic fracturing. The deformation and cracking behavior of the solid was studied by employing non-local ordinary state-based peridynamic theory, and the fluid flow along the crack was described based on the cubic law in cracking elements. To describe the fluid–solid interaction under the peridynamic framework, an equivalent term which presents the hydraulic pressure acting on newly generated crack surfaces was introduced into the equations of motion of material points. The model and approach were validated through investigating typical hydraulic fracture examples and comparing the results with experimental data and results in literature. The effect of weakness plane on hydraulic fracture in rock-like media was analyzed further. It is shown that the proposed model and approach inherits the advantages of peridynamics in handling fracturing, and is capable of reflecting fluid–solid interaction and fluid pressure along new-born crack surfaces accurately and efficiently.